1991
DOI: 10.1111/j.1600-0447.1991.tb05580.x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate study of simultaneous escape from suppression by dexamethasone of urinary free cortisol, plasma cortisol, adrenocorticotropic hormone and β‐endorphin in melancholic patients

Abstract: To investigate the relationships between pre- and postdexamethasone hypothalamic-pituitary-adrenal (HPA) axis functioning in depression, we measured the levels of baseline and postdexamethasone urinary free cortisol (UFC), plasma cortisol, adrenocorticotropic hormone (ACTH) and beta-endorphin. We found that dexamethasone significantly suppressed all hormone levels. All 4 postdexamethasone hormones--but not their baseline levels--were significantly higher in melancholic subjects than in minor and simple major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 73 publications
1
14
0
1
Order By: Relevance
“…In the present study, there was a highly significant effect of dexamethasone administration on plasma 13-endorphin levels. This is in accordance with previous findings (Wiedemann et al 1979;Smith et al 1981;Krantz and Brown 1985;Gispen-de-Wied et al 1987;Maes et al 1990Maes et al , 1991b. The frequency of 13-endorphin nonsuppression (defined as post-DST 13-endorphin 2: 22 pg/ mL; Maes et al 1990) in the present study was rather low, that is, 13.8%, compared to that in our previous studies (e.g., Maes et al 1990Maes et al , 1991b.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, there was a highly significant effect of dexamethasone administration on plasma 13-endorphin levels. This is in accordance with previous findings (Wiedemann et al 1979;Smith et al 1981;Krantz and Brown 1985;Gispen-de-Wied et al 1987;Maes et al 1990Maes et al , 1991b. The frequency of 13-endorphin nonsuppression (defined as post-DST 13-endorphin 2: 22 pg/ mL; Maes et al 1990) in the present study was rather low, that is, 13.8%, compared to that in our previous studies (e.g., Maes et al 1990Maes et al , 1991b.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies also report a suppression of plasma 13-endorphin levels by dexamethasone (Krantz and Brown 1985;Gispen-de-Wied et al 1987). This suppression may parallel the suppression of plasma ACTH levels following dexamethasone administration (Wiedemann et al 1979;Smith et al 1981;Maes et al 1991bMaes et al , 1994. Some (Gispen-de-Wied et al 1987;Maes et al 1990), but not all (Lin et al 1986;Ball et al 1987), found a higher escape of plasma 13-endorphin in major depressed subjects than in normal controls or DST cortisol nonsuppressors versus suppressors.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…On the cortex, both EFFECTS OF HYPERICUM PERFORATUM ON NEUROTRANSMITTERS hypericum extracts have similar effects, whereas changes in the 5-HT and noradrenaline content of the brainstem and diencephalon suggest other considerations. Increased activity of the hypo-thalamic±pituitary±adrenal axis in depression has been reported (Maes et al 1991) and it has also been proposed that abnormality of monoamine function plays a role in the pathogenesis of this disorder (Mokrani et al 1997). This disturbance is related to central corticotropin-releasing hormone hypersecretion (Holsboer et al 1992) and subsensitivity in negative feedback by glucocorticoids (Gomez et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the detection limit of the ultrasensi tive intact ACTH assay is 1 pg/ml, whereas previous assays had a sensitivity between 8 and 20 pg/ml [4][5][6][7]. In our previous studies, we have suggested that the type of ACTH assay employed to measure ACTH, i.e., intact [6,7] versus nonintact ACTH [4,5] may determine the clini cal relevance for the pathophysiology of major depression and DST cortisol nonsuppression. First, post-DST intact ACTH -but not nonintact ACTH -values are able to discriminate melancholia from minor depression and the healthy state.…”
Section: Introductionmentioning
confidence: 99%